Youth in View of the Issue of School Violence - Dubis, Malgorzata; Karbowniczek, Jolanta (European Scientific Journal, ESJ, 2018)
Violence and aggression has become common phenomena in modern world, they include almost all fields of social life. The reflection of problems the society copes with, is visible in the way of perceiving the educational values by pupils and their behaviour at school. The nature of the educational process organised by school is mainly the interactions among teachers and pupils and pupils themselves. They are not always the best. The anxiety among guidance counsellors and psychologists raises the fact that the cooperation rule and mutual help are replaced by the rule of dominance, extortion and force. The cases of ignoring the teacher’s orders are more and more common, lack of respect towards the teaching staff, humiliating adults and vandalism. Pupils battle against teachers and peers too. The school hall is a kind of arena of undesirable behaviours. Therefore, the school as an institution in which children and young people spend 1/3 of their time during the day, should not only deal with teaching but take an active part in the implementation of activities in the field of broadly understood prevention and upbringing. Therefore there are challenges in front of the school aiming at stopping, limiting or even eliminating negative behaviours from children’s and teenagers’ lives.